Setting Standards for Child‐Inclusive Restorative Justice. (8th February 2021) - Gal, Tali
Abstract : Childhood victimization occurs everywhere: in homes, kindergartens and schools, in state‐care institutions, neighborhoods, workplaces, and online. The most vulnerable children are least likely to disclose their victimization and see their cases prosecuted. Restorative justice (RJ) offers an alternative way for addressing criminality. It promotes accountability and reparation, without the debilitating effects of incarceration. RJ places victims at the center and enables them to communicate with perpetrators, usually with state monitoring. Recent decades have seen the widespread use of RJ worldwide. Yet, despite indications that RJ reduces violent crime, most programs target cases involving misdemeanors, juveniles, and first‐time offenders. Childhood victimization has generally been left outside the scope of RJ programs, apart from juvenile offending, where the main goal is offender rehabilitation. Consequently, when the victim is a child, the promise of RJ to give victims a voice is often unfulfilled. The high rates of childhood victimization and the shortcomings of criminal justice systems in prosecuting such crimes highlight the need for child‐inclusive RJ programs targeting crimes against children. The present article reviews findings from the fields of RJ, children's rights, psychology, and victimology. Through integrating these practices and approaches, it proposes a set of standards for developing child‐inclusive RJ programs. Practitioner's Key Points: Offers practical tips for implementing restorative justice with children. Explains child‐inclusiveness. Demonstrates that involving children in justice making is hard but beneficial for them. Explains how to involve children safely in decision‐making. Demonstrates that children want to have a voice, not necessarily a decision‐making power. Presents connection, continuity, and respectful listening as key features for children.